If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + 2(1 + -1p) = 2p + -2(1 + -1p) 2p + (1 * 2 + -1p * 2) = 2p + -2(1 + -1p) 2p + (2 + -2p) = 2p + -2(1 + -1p) Reorder the terms: 2 + 2p + -2p = 2p + -2(1 + -1p) Combine like terms: 2p + -2p = 0 2 + 0 = 2p + -2(1 + -1p) 2 = 2p + -2(1 + -1p) 2 = 2p + (1 * -2 + -1p * -2) 2 = 2p + (-2 + 2p) Reorder the terms: 2 = -2 + 2p + 2p Combine like terms: 2p + 2p = 4p 2 = -2 + 4p Solving 2 = -2 + 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. 2 + -4p = -2 + 4p + -4p Combine like terms: 4p + -4p = 0 2 + -4p = -2 + 0 2 + -4p = -2 Add '-2' to each side of the equation. 2 + -2 + -4p = -2 + -2 Combine like terms: 2 + -2 = 0 0 + -4p = -2 + -2 -4p = -2 + -2 Combine like terms: -2 + -2 = -4 -4p = -4 Divide each side by '-4'. p = 1 Simplifying p = 1
| 3(x-2)=9x-5 | | X+1.5y=30 | | V/18=7 | | -27+4n=36 | | d/5=-60 | | 25t=12/25 | | 24-(2c-3)=2(c+3)+c | | y+15.2=-4.5 | | 10x-4+6x=18 | | 7a+6a+7b-6b-10a= | | 3x-4.2=9.4 | | 8s-240=72 | | (6x)(3x+2)=y | | B+23m=342 | | -2p+4(1-p)=8p-2(1-p) | | 4+3a=22+a | | 4(5x+2)-8(x-6)=62 | | 2Q+D=48 | | B+10m=147 | | 7g-2h=-9 | | -2-16=3(h-2) | | 90+(5x-6)+3x=180 | | 2x+10-4x=-3 | | 4x+5=(-11) | | Y=5(3x-3)+2 | | 3/4(2x-4) | | B+10m=342 | | lnx^5=1 | | 21x/7-5x=24 | | 5/6(-2)p | | 2y/3-14/15=y/5 | | 27m^3+9m^2-12m-4=0 |